Soilwater Conductivity Analysis to Date and Locate Clandestine Graves of Homicide Victims1. Issue 4 (17th July 2015) - Pringle, Jamie K.; Cassella, John P.; Jervis, John R.; Williams, Anna; Cross, Peter; Cassidy, Nigel J.
Abstract In homicide investigations, it is critically important that postmortem interval and postburial interval (PBI) of buried victims are determined accurately. However, clandestine graves can be difficult to locate; and the detection rates for a variety of search methods (ranging from simple ground probing through to remote imaging and near‐surface geophysics) can be very low. In this study, simulated graves of homicide victims were emplaced in three sites with contrasting soil types, bedrock, and depositional environments. The long‐term monthly in situ monitoring of grave soil water revealed rapid increases in conductivity up to 2 years after burial, with the longest study evidencing declining values to background levels after 4.25 years. Results were corrected for site temperatures and rainfall to produce generic models of fluid conductivity as a function of time. The research suggests soilwater conductivity can give reliable PBI estimates for clandestine burials and therefore be used as a grave detection method.